2013
DOI: 10.1002/pon.3459
|View full text |Cite
|
Sign up to set email alerts
|

Early retirement and non‐employment after breast cancer

Abstract: Differences in ill health and functional status between various groups of non-employed cancer survivors need to be considered when planning policy measures for improving the labour market participation of this population and preventing their early withdrawal from working life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 35 publications
6
62
1
6
Order By: Relevance
“…Our findings show that patients with a desire to retire early have higher levels of psychological distress, anxiety and particularly depression, and a lower quality of life along all dimensions. This result is consistent with previous research investigating associated factors of early retirement in cancer patients (Carlsen et al., ; Lindbohm et al., ; Singer et al., ). However, we were not able to determine whether the poorer psychological status of patients with the desire to retire early is a result of the disease and cancer treatments, of difficult living and working conditions or both.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings show that patients with a desire to retire early have higher levels of psychological distress, anxiety and particularly depression, and a lower quality of life along all dimensions. This result is consistent with previous research investigating associated factors of early retirement in cancer patients (Carlsen et al., ; Lindbohm et al., ; Singer et al., ). However, we were not able to determine whether the poorer psychological status of patients with the desire to retire early is a result of the disease and cancer treatments, of difficult living and working conditions or both.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with previous studies on cancer patients and orthopaedic patients (Böttcher, Steimann & Ullrich et al., ; Bürger et al., ; Lindbohm et al., ) and populations samples (Lamberg, Virtanen, Vahtera, Luukkaala, & Koskenvuo, ). They are not only relevant for the development and implementation of multi‐professional rehabilitation and occupational therapy programmes (Désiron, Donceel, de Rijk, & van Hoof, ), but also for longer term follow‐up programmes to improve the labour market participation in cancer patients (de Boer, ; Mehnert, Harter, & Koch, ; Mehnert et al., ; Tamminga, de Boer, Verbeek, & Frings‐Dresen, ).…”
Section: Discussionsupporting
confidence: 93%
“…Early retirement can be due to many factors, particularly a catastrophic disease. In one study, early retirement was found to be related to a diagnosis of breast cancer with accompanying pain, comorbidities, and lower physical quality of life …”
Section: Retirement In Non‐nursing Literaturementioning
confidence: 99%
“…18,57 As BCS experience reduced employment, suffer from fatigue and anxiety, and experience varying levels of cognitive impairments associated with treatment, the amount of positive cognitive stimulation (e.g., interactions with coworkers, learning new tasks) and physiological support to the brain (e.g., having a steady/consistent sleep schedule) may be reduced as a result.…”
mentioning
confidence: 99%